AUTHENTIC ASSESSMENT E-LEARNING PROGRAM IN LEARNING WRITING SCIENTIFIC WORKS - Ai Siti Zenab; Yeni Rostikawati (JLER (Journal of Language Education Research), 2020)
Electronic learning system or better known as e-learning (electronic learning) is a learning program designed using web-based computer networks and the internet. The use of this system in Indonesian tertiary institutions continues to grow annually. One reason this system continues to evolve is that it is considered effective for distance learning and can help a wider area with more students. Besides, the system causes students and teachers not to use a protocol system that shows its rigid nature. Lectures run more flexibly by sticking to the final results already listed in the curriculum. To measure the level of success of a learning process evaluation is needed. One type of evaluation that can be used is authentic assessment. This assessment involves all the processes carried out in each lecture activity starting from the process, attitude, results. The research method used is descriptive qualitative. The results obtained were 86.21% of students actively involved in the lecturing process. For assignment grades, 31.03% of students received an Excellent grade (SB), 65.52% received a good grade (B). For the UTS score, the highest value obtained in the Good criteria (B) is 52.72%. The rest are in the Fair (C) and less (K) criteria. For UAS, the highest score depends on the Good criteria (B) 65.52%, while the rest depends on sufficient criteria and requires improvement. From the results of these data, it is evident that e-learning lectures require additional evaluations for each meeting, periodic checks, and fast responses to complaints expressed by students both related to teaching materials and those related to the system. Keywords: Authentic Assessment, Writing Scientific Papers, E-Learning